Ultrasonic collaborative pulse extraction of sugarcane polyphenol with good antiaging and α-glucosidase inhibitory activity - Zhuo, Gu; Xiong, Fu; Ping-Ping, Wang; Chin-Ping, Tan; Chun, Chen (Elsevier B.V., 2025)
Sugarcane, as one important and heavily planted industrial crop, is meaningful to develop its byproducts. In this paper, the ultrasonic collaborative pulse was beneficial for the yield improvement and good bioactivity protection. The sugarcane polyphenol extract (SPE) yield reached 2.42 ± 0.08 mg/g DW at the optimized conditions: pulse time of 60 s, pulse intensity of 2 kV/cm, ultrasonic time of 90 min, and ultrasonic power of 120 W. The SPE contained the total phenolic content of 6.01 ± 0.12 mg GAE/g extract and total flavonoids content of 7.15 ± 0.24 mg RE/g extract. The SPE was mainly composed of chlorogenic acid, schaftoside, hyperoside, quercitrin, and trans-3-hydroxycinnamic acid with 10.24 %, 14.92 %, 4.22 %, 12.05 %, 25.54 %, respectively. The SPE showed good radical scavenging activity with ORAC value of 134.57 μmol/g. The SPE could reduce the oxidative stress and extend the mean lifespan of nematodes by 7.19 % in vivo through increasing the activity of SOD and CAT to decrease the ROS level and MDA content. In addition, the SPE showed strong α-glucosidase inhibitory activity with IC50 of 0.53 mg/mL in a mixed inhibition type, which suggested that the SPE had good hypoglycemic potential.